2019
DOI: 10.2196/mhealth.9967
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Attrition in a Text-Based Nutrition Education Program: Survival Analysis of Text2BHealthy

Abstract: BackgroundText-based programs have been shown to effectively address a wide variety of health issues. Although little research examines short message service (SMS) text messaging program characteristics that predict participant retention and attrition, features of SMS text message programs, such as program duration and intensity, message content, and the participants’ context, may have an impact. The impact of stop messages—messages with instructions for how to drop out of an SMS text message program—may be pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…In contrast, psychedelic-specific factors were found to be poor predictors of attrition. Methods for reducing attrition, which have been validated through other fields, such as text messaging [ 86 ], gamification [ 87 , 88 ], monetary incentives [ 89 , 90 ], or the creation of web-based participant communities [ 91 ], are thus likely to be applicable also to observational studies on psychedelics, which should be investigated in future studies. While not without prevailing limitations, for which there is significant scope for improvement, these findings somewhat support the reliability and validity of large-scale prospective web-based data collection as a methodology for studying the predictors and processes of changes related to psychedelic use.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, psychedelic-specific factors were found to be poor predictors of attrition. Methods for reducing attrition, which have been validated through other fields, such as text messaging [ 86 ], gamification [ 87 , 88 ], monetary incentives [ 89 , 90 ], or the creation of web-based participant communities [ 91 ], are thus likely to be applicable also to observational studies on psychedelics, which should be investigated in future studies. While not without prevailing limitations, for which there is significant scope for improvement, these findings somewhat support the reliability and validity of large-scale prospective web-based data collection as a methodology for studying the predictors and processes of changes related to psychedelic use.…”
Section: Discussionmentioning
confidence: 99%
“…Dropout is primarily related to the program provider, outline of the intervention, activity in the platform (engagement), and, to a lower degree, the demographic variables available in this study. Multiple other studies have found attrition to be related to demographic variables [22,15], but these were not available in this dataset.…”
Section: Discussionmentioning
confidence: 99%
“…However, survival analysis can also be applied to other contexts. For instance, recent studies used survival analysis to evaluate students’ engagement within online learning environments [8] , [9] , [10] , [11] , [12] , [13] , [14] . In this study, we applied this approach to evaluate students’ engagement – and, conversely, dropout rates – over time for different time periods as observed for the online learning environment Bettermarks .…”
Section: Introductionmentioning
confidence: 99%